Diagnostic and Pathophysiological Impact of Myocardial MIBG Scintigraphy in Parkinson's Disease - Jörg Spiegel (Parkinson's Disease, 2010)
Myocardial MIBG scintigraphy is established in the diagnosis and differential diagnosis of Parkinson's disease (PD). Numerous studies address the pathophysiological impact of myocardial MIBG scintigraphy: the myocardial MIBG uptake correlates with the clinical phenotype of PD; the background of this phenomenon is unclear. Furthermore MIBG scintigraphy enables to study the extracranial Lewy body type-degeneration. In combination with cerebral dopamine transporter imaging, MIBG scintigraphy allows to correlate cerebral and extracranial Lewy body type-degeneration in PD.